2017
DOI: 10.18632/oncotarget.16519
|View full text |Cite
|
Sign up to set email alerts
|

A six-microRNA signature in plasma was identified as a potential biomarker in diagnosis of esophageal squamous cell carcinoma

Abstract: The differential expression of microRNAs (miRNAs) in plasma of esophageal squamous cell carcinoma (ESCC) patients may serve as a diagnostic biomarker. A four-stage study was conducted to identify plasma miRNAs with potential in detecting ESCC. Exiqon panels (2 ESCC pools vs. 1 normal control (NC) pool) were applied in the screening phase to obtain miRNA profiles. The identified miRNAs were further evaluated through training (36 ESCC VS. 42 NCs) and testing stages (101 ESCC VS. 113 NCs) with qRT-PCR assays. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 59 publications
(59 reference statements)
3
43
0
Order By: Relevance
“…Moreover, exosomal miR‐106a‐5p expression was shown to be negatively correlated with patient QMGS, indicating its association with MG clinical typing and severity. Interestingly, one of the dysregulated miRNAs by deep‐sequencing in the present study, miR‐106a‐5p has been previously shown to be associated with the pathogenesis of many cancers, including melanoma, colorectal and gastric cancer, MG, and esophageal squamous‐cell carcinoma . Similarly, miR‐106a‐5p dysregulation has been reported in T‐cells of patients with immune diseases, and may inhibit the proliferation, migration, and invasion of carcinoma cells by modulating various mRNA targets .…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, exosomal miR‐106a‐5p expression was shown to be negatively correlated with patient QMGS, indicating its association with MG clinical typing and severity. Interestingly, one of the dysregulated miRNAs by deep‐sequencing in the present study, miR‐106a‐5p has been previously shown to be associated with the pathogenesis of many cancers, including melanoma, colorectal and gastric cancer, MG, and esophageal squamous‐cell carcinoma . Similarly, miR‐106a‐5p dysregulation has been reported in T‐cells of patients with immune diseases, and may inhibit the proliferation, migration, and invasion of carcinoma cells by modulating various mRNA targets .…”
Section: Discussionsupporting
confidence: 59%
“…In colorectal cancer, miR‐106a was elevated in stool samples from patients with adenomas and colorectal cancer compared to healthy controls (Link et al ., ). In esophageal squamous cell carcinoma, miR‐106a upregulation in plasma was shown to be a diagnostic marker as part of a six‐miRNA signature (Zhou et al ., ). In a study of patients with breast cancer, Wang et al .…”
Section: Discussionmentioning
confidence: 97%
“…controls (Link et al, 2010). In esophageal squamous cell carcinoma, miR-106a upregulation in plasma was shown to be a diagnostic marker as part of a six-miRNA signature (Zhou et al, 2017). In a study of patients with breast cancer, Wang et al found that miR-106a was upregulated in breast tumor specimens and matched sera compared to normal controls .…”
Section: Discussionmentioning
confidence: 99%
“…What is more, it was revealed that miR‐106a‐5p might act as an anti‐apoptotic factor and could confer the cisplatin resistance of NSCLC cells by targeting ABCA1 . Circulating miR‐106a‐5p has been proved to show high levels in a wide range of other cancers, such as melanoma , colorectal cancer , gastric cancer , as well as esophageal squamous cell carcinoma . MiR‐93‐5p, as a miRNA in the miR‐106b~25 cluster and a paralog of the miR‐17~92 cluster, has been previously verified up‐regulated in NSCLC tissues .…”
Section: Discussionmentioning
confidence: 95%
“…Li et al. confirmed that up‐regulated miR‐93‐5p facilitated tumorigenesis and metastasis of NSCLC by activating oncogenic PI3K/Akt pathway through inhibition of LKB1, PTEN, and p21 expression . Meanwhile, miR‐93‐5p could enhance tumor angiogenesis of NSCLC by suppressing β ‐TRCP2 .…”
Section: Discussionmentioning
confidence: 98%